The antegrade flow pedicled medial sural artery perforator flap for knee soft-tissue reconstruction following high-voltage electrical burn injuries. Issue 4 (October 2022) - Santamaría Córdoba, Natalia; Déniz Martínez, Alejandro; Ayala Parra, David G.
Highlights: Knee joint features make it prone to high-voltage electrical burn injuries. In this scenario, knee soft-tissue reconstruction represents a challenging task. The pedicled MSAPF has not been described as an alternative in these cases. It is a reliable and valuable reconstructive alternative, especially in resource-limited settings. It provides pliable skin easily adaptable to the knee contour. Abstract: High-voltage electrical burn injuries are still a significant cause of admission to burn units worldwide, mainly in developing countries. They are commonly fatal and leave utterly significant sequelae in those who survive. Electrical energy can affect all body systems, causing impairment of the wound healing mechanisms through a robust inflammatory response mounted by the host. The musculoskeletal system is often involved, and indirect mechanisms harm joints due to its condition of electrical resistance transition zones. Reconstruction of knee soft tissues in this scenario represents an extraordinarily demanding task for any plastic surgeon, given knee joint complexity and significance in lower limb movement and gait. Likewise, the coverage of its critical structures, such as tendons, ligaments, and joint surfaces, must be the cornerstone. The current paper describes our experience using the pedicled medial sural artery perforator flap (MSAPF) to treat three patients with extensive patellar soft-tissue defects following high-voltage electrical burn injuries. To the best of our knowledge, it has not been reported before, and there is little awareness of the employment of perforator-based regional flaps in the reconstruction of burn injuries. In our experience, this alternative proved its reliability, low donor site morbidity, easy adaptability to knee contour and proper aesthetic potential, allowing patients to continue their functional rehabilitation speedily. Therefore, it should be considered a valuable reconstructive alternative, especially in resource-limited settings where microsurgical reconstructions with free flaps cannot be performed.